(untitled) (Práxis Educativa, 2020)
Abstract: The epistemological (theoretical-methodological) weaknesses of research and the little production of studies that discuss such issues in the field of education policy are pointed out by the literature as a challenge for the consolidation of the field and researchers’ education. Such notes have led to questions about the scientificity of such studies, which has placed to researchers the need of evaluating the research and its context of production, as well as the understanding of its characteristics, weaknesses and potentialities in order to improve the field and the study themes linked to education policy. With the intention of contributing to this debate, this paper aims to present the result of the analysis of 27 doctoral dissertations produced in Brazilian Graduate Programs in Education with a Doctorate, in the research lines of education policy, in the period 2010-2012, so as to verify the presence or not of the epistemological weaknesses pointed out by the literature. Keywords: Epistemological fragility. Analysis of doctoral dissertations. Education policy.